2004
DOI: 10.1007/s00262-004-0575-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of NK receptors and their ligands in melanoma patients: prevalence of inhibitory over activating signals

Abstract: Antitumor cytotoxicity of NK cells and T cells expressing NK-associated receptors is regulated by interaction between their cell surface killer immunoglobulin-like receptors (KIRs) and CD94/NKG2 heterodimers with MHC class I ligands on target cells. To test the hypothesis that KIR and/or HLA polymorphisms, and KIR/HLA combinations could contribute to the tumorigenesis, association studies were performed in 50 patients with malignant melanoma (MM) in different stages of disease and 54 controls. Our data showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 37 publications
3
32
2
1
Order By: Relevance
“…Consistent with our finding, a recent study showed that the presence of inhibitory KIR2DL2/2DL3 in association with their putative ligands was also increased in melanoma patients compared to healthy individuals. 7 Finally, we also found that 27.1% of patients who were heterozygous for KIR2DL2/2DL3 were also heterozygous for HLA-C1/C2 (versus 12.8% in the control group, P ¼ 0.020) (data not shown).…”
mentioning
confidence: 67%
“…Consistent with our finding, a recent study showed that the presence of inhibitory KIR2DL2/2DL3 in association with their putative ligands was also increased in melanoma patients compared to healthy individuals. 7 Finally, we also found that 27.1% of patients who were heterozygous for KIR2DL2/2DL3 were also heterozygous for HLA-C1/C2 (versus 12.8% in the control group, P ¼ 0.020) (data not shown).…”
mentioning
confidence: 67%
“…52 PCR-SSOP was carried out to confirm the presence or absence of KIR genes in Northern and Republic of Ireland populations as previously described. KIR gene and genotype frequencies of an additional 36 global population (4218 individuals from 38 different studies) were obtained from the published literature (35 populations [31][32][33]46,48,49,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] ) and from an online database www.allelefrequencies.net. 72 Genotypes were classified as follows: the absence of 2DL2, 2DL5, 3DS1, 2DS1, 2DS2, 2DS3 or 2DS5 indicates that an individual is homozygous for the A genotype (that is, AA).…”
Section: Kir Typingmentioning
confidence: 99%
“…11,12 KIRs are key receptors of human natural killer (NK) cells, a subset of lymphocytes that trigger early immune response against infection and tumors, while maintaining tolerance to healthy self. 13,14 Further, CD8 þ cytotoxic T lymphocytes (CTL) with memory phenotype and CD4 þ CD28 null T cells also express KIRs indicating KIRs' regulatory role in antigen-specific adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%